Collapse resistance analysis of composite beam–column substructure considering the location of column failure. (1st December 2022) - Duan, Shi-chao; Zhong, Wei-hui; Tan, Zheng; Gao, Di; Meng, Bao; Zheng, Yu-hui; Qiu, Ying-zhao
Abstract: In actual situations, it is not possible to determine the exact location where the column will fail (in a member or building structure). Based on the location of the failure, the lateral constraint stiffness of the directly affected area of the structure will change, affecting the structure's anti-collapse performance. This study aims to explore how the location of the failure column affects the collapse resistance of composite beam–column substructures; the double-sided restraint substructure (DSRS) and the single-sided restraint substructure (SSRS) were chosen as research objects, and the two test structures were subjected to static loading tests to compare their collapse resistance. The results showed that the two specimens had similar failure modes and deformation patterns. In addition, the development trend of the internal force of the two specimens was comparable, but the axial force of the SSRS was smaller. The contribution of the catenary mechanism of DSRS was approximately 24%, while the catenary effect of SSRS was not fully exerted, leading to only 15% of the total resistance. Two specimens were modeled in ABAQUS, and the finite element method was verified by comparing the simulation results with the test results. A full-scale model was established to analyze the effects of the lateral restraint stiffness of DSRS and SSRS and the side column size on the collapse resistance of the substructure. The finite element analysis results are as follows: (1) lateral restraint stiffness had less influence on the small deformation stage of the substructure; (2) the beam end tension force played a significant role in the collapse resistance of the substructure; (3) increasing the horizontal lateral restraint stiffness can effectively improve the anti-collapse performance of composite beam–column substructure; (4) the side column can provide effective axial and rotational restraint for the beam end. Having too large or too small a side column can have an adverse effect on the structure. Moreover, the larger the side column size, the better the continuous collapse resistance of the substructure when the beam–column linear stiffness ratio is between 0.6 and 1.1. Highlights: Two substructures considering the location of column failure were tested. Discuss the variation of lateral restraint stiffness affected the substructure. The optimum range of beam-column linear stiffness ratio was given. Providing designers with reference and related design advice.